Professional tennis and transnational law : contractual and regulatory / edited by Ilias Bantekas, Marko Begović. - Bantekas, Ilias; Begović, Marko (Cambridge University Press, 2025)
This book examines the intersection of professional tennis and legal regulation, unveiling a fascinating world where tennis meets domestic, international and transnational law, and showing the many ways these legal frameworks impact tennis. Filled with firsthand accounts of the legal landscape and its implication on tennis, the work provides an accessible, engaging portrait of the tennis ecosystem that is equally suited for academics, athletes, sports lawyers and journalists. It is an essential read for those working within sports law generally, and the tennis industry specifically. This title is also available as Open Access on Cambridge Core.